Uso de diferentes dosis de calcio y silicio para el mejor cuajado de frutos en el cultivo de pepinillo hibrido em americam slicer 160 f-1 en Lamas – San Martín - Mori Pizango, Martha Madeleide (2013)
This research paper, entitled "Use of different doses of calcium and silicon for better fruit set in cucumber cultivation Americam hybrid EM Lamas Slicer 160 f1-San Martin", were to: assess three (03) dose Calcium-three (03) of silicon in the agronomic performance of the crop of hybrid cucumber (Cucumis sativus L.) EM 160 Slicer Americam f1, in conditions of the province of Lamas, determine the best dose of calcium and silicon that will generate higher yields of fruit growing cucumber and perform economic analysis of treatments. This work was done in the farm "THE PACIFIC" owned Rivera Jorge Luis Pelaez, located in the district and province of Lamas, San Martin department. We used the statistical design of randomized complete block design (RCBD) with 3 blocks and 7 experimental treatments taking 21 units. The indicator was growing hybrid Em Pickle Slicer Americam 160 F1, in the seed company Acquired Manrique (Lima - Peru) provenance of America (USA) Purity 99%, 85% germination and contains approximately 5000 seeds per container. The treatments were: 03 doses of calcium (224, 300 and 350 kg / ha) and 03 Silicon doses (50, 100 and 150 kg / ha) and have an absolute control for both. The most significant findings were: application 150 kg ha-1 of Si and 350 kg ha-1 of Ca treatments were achieved with the best average 132,832.00 106,704.49 kg ha-1 and kg ha-1 resulting statistically equal each other, positive responses were linear increase in plant height, number of harvested fruits, fruit weight and length and performance Tn.ha-1 according to the application rates of Si and Ca and treatment with a dose of 150 kg ha-1 of Si, was the one that obtained the best performance with a net profit of S/.7368.56 and the highest percentage with 38.38% in profitability. Furthermore, treatment with higher doses of calcium (350 kg ha-1) was the next treatment that reached the second best result with a net profit of S /. 41.57.03 and with a return of 24.19%.